Photo Voice: Application of a Novel Assessment Tool to Identify the Need to Improve Water Safety in Mountain Communities in the Dominican Republic - Weier, Adam (My University, 2012)
The mountain communities in the Elias Pina province of the Dominican Republic have the highest prevalence rates of diarrheal disease in the country. Using the participatory method of Photo Voice, the researcher partnered with a local NGO to collect preliminary information that will assist with the process of improving water safety in these mountain communities. The three goals of the project were to: 1) learn where the communities collected their drinking and cooking water, 2) assess their understanding of safe water, and 3) empower the communities to find practical solutions to accessing safe water. Upon evaluation, the researcher recommended that education be provided on the attributes of safe water, the benefits of water purification and the proper chlorine-water ratio, and the characteristics of waterborne diseases.
21 p.
Keywords: Dietetics; Nutritional Sciences